Oncological vigilance in pediatric practice - Gawle-Krawczyk, Karolina; Łaguna, Paweł (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Annually in Poland, malignant neoplasms are diagnosed in approximately 1100–1200 pediatric patients. 5-year overall survival is observed in 81.2% of patients, reflecting substantial progress in pediatric oncology that encompasses enhanced diagnostic capabilities, innovative therapeutic agents, multimodal treatment strategies, and optimized supportive care protocols. However, classical manifestations of malignancy frequently overlap with benign pathologies commonly encountered in the pediatric population, contributing to delayed diagnosis and increased treatment failure rates. Consequently, comprehensive physical examination with heightened oncological awareness is imperative during routine clinical encounters. This vigilant approach may facilitate early neoplastic detection at lower clinical stages, thereby significantly improving prognostic outcomes and decreasing therapeutic toxicity.